Venado - Fulgueira, Pablo (Mexico, 2009)
A film about chanting shamans, their eternal journeys and celebrations. Around 300 days of travel and a journey of more than three thousand kilometers for their sacred places, Mexican “jicareros” comply with the Huichol wirrárika tradition guided by their songs and the "pig" or fire. In their wake, these men are leaving offerings for a life without diseases.
Verzio Film Festival Submission
Keywords: Documentary films